2018
DOI: 10.3390/min8040150
|View full text |Cite
|
Sign up to set email alerts
|

The Influencing Mechanisms of Sodium Hexametaphosphate on Chalcopyrite Flotation in the Presence of MgCl2 and CaCl2

Abstract: Sea water has been used in flotation plants, showing a promising way to save fresh water usage. Previous studies indicated that divalent salts in sea water played negative roles in chalcopyrite flotation, but not much work have been conducted to understand the eliminating mechanisms. This study systematically investigated the effects of divalent cations of Ca 2+ and Mg 2+ on natural flotability of chalcopyrite in the absence of collectors and frothers. The reduced recovery was mainly due to the adsorption of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 54 publications
4
27
0
1
Order By: Relevance
“…It should be noted that the depressing effect due to MgCl 2 was more apparent than that of CaCl 2 . Although Nagaraj and Farinato [45] reported that Ca 2+ had a negligible effect on Mo floatability, many other studies indicated that both Mg 2+ and Ca 2+ played negative roles on sulfide mineral flotation, [22,23,26,29,46], consistent with this study. The differences were probably due to the different mineral samples and flotation conditions used.…”
Section: Theory Calculationsupporting
confidence: 88%
See 2 more Smart Citations
“…It should be noted that the depressing effect due to MgCl 2 was more apparent than that of CaCl 2 . Although Nagaraj and Farinato [45] reported that Ca 2+ had a negligible effect on Mo floatability, many other studies indicated that both Mg 2+ and Ca 2+ played negative roles on sulfide mineral flotation, [22,23,26,29,46], consistent with this study. The differences were probably due to the different mineral samples and flotation conditions used.…”
Section: Theory Calculationsupporting
confidence: 88%
“…Both froth concentrates and tailing were filtered and air dried at 70 • C prior to weighing. The concentrations of Ca 2+ (0.01 M) and Mg 2+ (0.05 M) selected in this study were the same as those contained in seawater [23], thereby providing evidence to understand the primary ions playing the most significant inhibition role. The recovery shown in the Figures 4-6 was the average value of three repeated experiments, with the error bar being as one standard deviation.…”
Section: Minerals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, la fuerza iónica no es el único aspecto que se debe considerar respecto al agua de mar, ya que a condiciones altamente alcalinas los iones de calcio y magnesio se hidrolizan en la forma de CaOH + /MgOH + y surgen complejos que precipitan como Ca(OH)2/Mg(OH)2. Estas especies, cuya concentración depende del pH y la concentración inicial de cada elemento, han mostrado ser muy perjudiciales en operaciones de flotación de sulfuros, ya que su capacidad para adherirse a la superficie de algunos minerales conduce a que estos pierdan hidrofobicidad y consecuentemente disminuyan su flotabilidad (Castro, 2012;Jeldres et al, 2017aJeldres et al, , 2016Li et al, 2018;Ruan et al, 2018). Menor es la información disponible acerca del impacto que genera la formación de estos complejos en operaciones de espesamiento.…”
Section: Introductionunclassified
“…This excessive addition of lime means a considerable extra cost to the process, in addition to an increase of water hardness. (ii) Calcium and magnesium ions precipitate, which significantly affects the recovery of molybdenite and copper sulfides [16][17][18][19]. For these reasons, one of the main recommendations is working at a natural pH (or close to it), separating pyrite through the addition of new depressants reagents.…”
mentioning
confidence: 99%